Aplicación de un plan de acompañamiento para mejorar el desempeño de estudiantes de Educación Superior - Paredes Ruiz, Aide (2018)
This research arises from a study that was developed at Br. Victorino Elorz Goicoechea Higher Pedagogical Education Institute of Cajamarca during the plan of a pedagogical accompaniment application to improve the performance of this institution’s students in the academic semester 2018-I. The methodology used goes according to the quantitative approach. The investigation is applied. The research design is quasi-experimental, the sample is represented by 13 students of the Primary Education and Technology-Science and Environment study program. It was used rubrics provided by the Education Ministry as an instrument to pick up information to evaluate the teaching performance and the practice supervision sheets of Br. Victorino Elorz Goicoechea IESP, the rubrics were applied in two moments, as a pretest at the beginning of the pre-professional practice and at the time departure as a post-test and, the sheets were used to record the scores of eight observations. The results obtained for the general hypothesis were submitted to the T-student statistical test for related samples for the following reasons: it has to be applied to a same group in two different measures at different times, therefore, it is a longitudinal study, the permanent variable creates two measures, one before and one after. _x000D_ The random variable are the qualifiers obtained as a result of the pedagogical accompaniment; this is a numerical variable. It has been possible to demonstrate that in the sample of size 13, the p value found is 0.00, lower than the significance level chosen, that is why the hypothesis of the researcher is accepted